Evaluation of Macular Function Using Pattern Electroretinogram in Idiopathic Epiretinal Membrane. Issue 5 (September 2015) - Shin, Min Kyu; Kim, Sung Il; Park, Sung Who; Byon, Ik Soo; Kim, Hyun Woong; Lee, Ji Eun
<x xml:space="preserve">Abstract</x> Purpose Pattern electroretinogram (PERG) in idiopathic epiretinal membrane (ERM) was investigated to find the correlation of the ganglion cell function with postoperative visual acuity. Design This was a retrospective consecutive chart review. Methods Medical records of 24 eyes that underwent vitrectomy and membrane peeling for idiopathic ERM were reviewed retrospectively. The amplitude and implicit time of P50 and N95 in preoperative PERG were analyzed to find correlation with visual acuity and foveal thickness. The ratio of the parameters in involved eyes to those in healthy fellow eyes was calculated for analysis. Results Visual acuity (logarithm of the minimum angle of resolution) improved from 0.53 at baseline to 0.34 at 6 months (P = 0.003). Foveal thickness decreased significantly from 488.3 μm at baseline to 374.7 μm (P = 0.001). The preoperative N95 amplitude ratio was significantly correlated with visual acuity at 6 months after ERM removal (r = −0.423, P = 0.040), whereas the amplitude of P50 and implicit time of both waves showed no significant correlation with postoperative visual acuity. The implicit time ratio of P50 (r = 0.530, P = 0.008) and N95 (r = 0.436, P = 0.033) showed significant correlation with preoperative foveal thickness on optical coherence tomography. Conclusions N95 amplitude in PERG was a predictor of visual outcomes after ERM surgery. These results suggest the correlation of postoperative visual acuity with the function of the ganglion cell layer, which is the closest cell layer to be affected by ERM.